Induction of human antigen-specific and non-specific helper factors in vitro. - Kantor, F (1979)
Human peripheral blood leucocytes, cultured for 4--6 days with the appropriate concentration of protein or synthetic polypeptide antigen, yield helper cells. These cells, after a further 24 hr incubation with the appropriate antigen release helper factors, which are of two types, antigen specific and non-specific; a similar situation to that described in the mouse. These factors are assayed by their effects on the plaque-forming cell response of mouse spleen cells cultures in vitro. The potential applications of this new assay for human T cell function are discussed.